Development of lithium ion power system for satelite - Mohd. Amir Iskandar, Mazlan; Kamal irfan, Ahmad Shakir; Zulkifli, Abdul Aziz (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/